Per- and poly-fluoroalkyl substances (PFAS) and female reproductive outcomes: PFAS elimination, endocrine-mediated effects, and disease - Rickard, Brittany P.; Rizvi, Imran; Fenton, Suzanne E. (Toxicology (Amsterdam), 2022)
Per- and poly-fluoroalkyl substances (PFAS) are widespread environmental contaminants frequently detected in drinking water supplies worldwide that have been linked to a variety of adverse reproductive health outcomes in women. Compared to men, reproductive health effects in women are generally understudied while global trends in female reproduction rates are declining. Many factors may contribute to the observed decline in female reproduction, one of which is environmental contaminant exposure. PFAS have been used in home, food storage, personal care and industrial products for decades. Despite the phase-out of some legacy PFAS due to their environmental persistence and adverse health effects, alternative, short-chain and legacy PFAS mixtures will continue to pollute water and air and adversely influence women’s health. Studies have shown that both long- and short-chain PFAS disrupt normal reproductive function in women through altering hormone secretion, menstrual cyclicity, and fertility. Here, we summarize the role of a variety of PFAS and PFAS mixtures in female reproductive tract dysfunction and disease. Since these chemicals may affect reproductive tissues directly or indirectly through endocrine disruption, the role of PFAS in breast, thyroid, and hypothalamic-pituitary-gonadal axis function are also discussed as the interplay between these tissues may be critical in understanding the long-term reproductive health effects of PFAS in women. A major research gap is the need for mechanism of action data – the targets for PFAS in the female reproductive and endocrine systems are not evident, but the effects are many. Given the global decline in female fecundity and the ability of PFAS to negatively impact female reproductive health, further studies are needed to examine effects on endocrine target tissues involved in the onset of reproductive disorders of women.